“Stalinist architecture”: Reflected in modern research almost a hundred years later - I. Ε. Pechenkin (Шаги)
The article provides a review of up-to-date academic knowledge of Soviet architecture of the 1930s–1950s, usually labeled in public discourse as Stalinist, as if the Soviet dictator was in fact its true supreme author. Of course, it is impossible to cover in one article the whole variety of problems associated with the study of the phenomenon of Stalinist architecture. For this reason, the author’s attention is focused on the most significant research trends. First of all, these include the search for the most appropriate terminology that would allow one to avoid excessive journalisticism (like the popular phrase “Stalinist Empire style”), would reflect the internal dynamics of the architectural process over the course of two decades, and would designate the place of Soviet architecture in the global context (primarily the Western one). From the point of view of methodology, the empirical approach still prevails, and the stage of identifying and systematizing the material is actually continuing. At the same time, the importance of microhistorical and biographical studies dedicated to specific regions and particular personalities is significantly increasing. Among a number of factors that negatively affect the research process, it is necessary to note the tendency towards politicization and re-ideologization of academic discourse in architectural history.